2021
DOI: 10.1111/iju.14612
|View full text |Cite
|
Sign up to set email alerts
|

An Italian multicenter analysis of emergency admissions and treatment of upper tract urolithiasis during the lockdown and reopening phases of the COVID‐19 pandemic: Are we ready for a second wave of the outbreak?

Abstract: Objectives: To assess if the lockdown period (March-April 2020) during the coronavirus disease-19 outbreak in Italy influenced the number, presentation, and treatment of urgent admissions to the emergency department for ureteral lithiasis, and to evaluate the same variables during the reopening phase (May-June 2020). Methods: We performed a retrospective analysis of patients admitted to the emergency department of three different hospitals (two coronavirus disease-19 hubs). Demographics and data on acute pyelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Castellani et al. [26] compared ureteric stone disease outcomes of 298 patients prior to the pandemic with 218 patients during the pandemic, reporting reduced admissions and higher rates of infected‐obstructed systems, hospitalisation, and intervention during the COVID‐19 pandemic. Furthermore, Flammia et al.…”
Section: Discussionmentioning
confidence: 99%
“…Castellani et al. [26] compared ureteric stone disease outcomes of 298 patients prior to the pandemic with 218 patients during the pandemic, reporting reduced admissions and higher rates of infected‐obstructed systems, hospitalisation, and intervention during the COVID‐19 pandemic. Furthermore, Flammia et al.…”
Section: Discussionmentioning
confidence: 99%
“…The number of admissions in the reopening phase (May-June 2020) was in line with that in 2019 (n = 138). However, the frequency of hospitalizations, acute obstructive pyelonephritis and complications was significantly higher during lockdown compared to 2019 22 . In contrast, our work revealed that the whole number of elective and urgent surgical procedures were similar.…”
Section: Discussionmentioning
confidence: 82%
“…A similar analysis was conducted in Italy during the lockdown period between March and April 2020, showing a significant reduction in symptomatic ureteral lithiasis admission of 51.2%. Most of the patients hospitalized had complicated disease and required an increased rate of interventional procedures compared to the equivalent period in 2019 [29]. Patients presenting with renal colic preferred oral analgesics over SWL and i.v.…”
Section: Discussionmentioning
confidence: 99%